SISTEM PAKAR ANALISA KERUSAKAN PADA SEPEDA MOTOR HONDA BEAT INJECTION DENGAN METODE BACKWARD CHAINING - Riki Siregar (PETIR, 2018)
Expert system is one part of artificial intelligence designed to mimic the expertise of an expert in answering questions and completing a problem. This application made to resolve damages acquired from the symptoms which mostly encountered by motorcyclist. This application created by backward chaining using backward tracking method that works based on conclusions from series of happenings. In this study, collecting the data gained from the experts involved in the existing system by direct interview, direct observation and also from the literatures as references to support the explanation of the elements studied. The objective of this application is to help the mechanics or technicians in analyzing damages occured in Honda Beat Injection motorcycle at the garage in Honda Motor Festival faster.